Adaptation, attenuation and molecular characterisation of very virulent infectious bursal disease virus for development of tissue culture-based attenuated and inactivated vaccines - Lawal, Nafi'u (2018)
Infectious bursal disease (IBD) is an important viral disease of chickens worldwide that causes high mortality, immunosuppression and serious economic loss in poultry industry that can only be prevented by proper vaccination and biosecurity programmes. The disease is endemic in Malaysia. Although IBD vaccines have been produced successfully using chicken eggs, but high cost, limited supply of specific pathogen free (SPF) eggs and possible contamination by viruses of avian origin limits the use of eggs as a tool for vaccine production. Currently, IBD vaccines mostly produced using classical (ca) and variant (va) IBDV as seed virus are SPF egg based. However, the high level of maternal antibody in chicks induced by the vaccine can be neutralized by vvIBDV. The vvIBDV strain also was reported to be difficult to adapt to tissue cultures in vitro It was the objectives of this study to determine suitable tissue cultures for the adaptation, propagation and attenuation of vvIBDV and produce a suitable live attenuated and inactivated IBDV isolates for vaccine development using bioreactor technology. Two Malaysian vvIBDV strains UPM0081 (also known as B00/81) and UPM190 (also known as UPM04/190) isolated from local IBD outbreaks were serially passaged in SPF embryonated chicken eggs via the chorioallantoic membrane (CAM) route for up to 12 passages. The isolates were then further adapted and propagated into chicken embryo fibroblast (CEF), Vero and BGM-70 cell lines for 10, 10 and 20 consecutive passages, respectively. The molecular characteristics of the vvIBDV at different passages were identified, analyzed and phylogenetic trees were constructed. Selected isolates passaged either in SPF embryonated chicken eggs or cell lines were further propagated in BGM-70 cell line using bioreactor. The pathogenicity, immunogenicity and efficacy of attenuated and inactivated of these vvIBDV isolates were determined in chickens. The study showed that 75% cytopathic effect (CPE) was developed in CEF following propagation of the UPM190 vvIBDV at passage 5 (P5) with the virus titre of 106.28TCID50/mL. The UPM0081 vvIBDV was similarly adapted at P5 with 75% CPE and a titer of 105.5TCID50/mL. In the Vero cells, 75% CPE was recorded at P5 and became 100% by P10 within 7days pi with virus titer of 105.5 TCID50/mL for UPM190. The UPM0081 similarly adapted at P1with the same CPE pattern, and by P5 the CPE was 75% with a virus titer of 104.62 TCID50/mL. Adaptation of UPM190 in BGM-70 cell line was achieved as early as P1 and was more prominent at P5 with a virus titer of 109.5 TCID50/mL. Based on the titers obtained, BGM-70 cell line was selected for further propagation until the CPE became subtle at P18 and P19 for UPM0081 and UPM190, respectively. The serial passaging was finally stopped at P20. The CPE pattern was observed in BGM-70 cells inoculated with UPM190 isolate started at 50% CPE and gradually increased up to 100% at P9 and fall to 25% by P20 with a virus titer of 109.5 TCID50/mL at P5. The UPM0081 exhibited similar adaptation and CPE pattern with UPM190 except that the titer was 109.2 TCID50/mL at P5 and the CPE was 25% at P1 and fell to 25% by P20. The CPE pattern was similar in all the cell lines characterized by cell rounding, cytoplasmic vacoulation and granulation as well as detachment from flask. The UPM0081 inoculated and adapted in SPF embryonated chicken eggs resulted in hyperemia, ecchymotic hemorrhages in the thigh and breast muscles, greenish to yellowish liver and intracranial hemorrhages. The UPM190 showed abdominal distension, subcutaneous edema, intracranial hemorrhages and mottled liver of the infected embryo. Both CAM and cell culture samples at various passages were positive for vvIBDV by RT-PCR and sequencing. Sequence analysis using MEGA v.7 and BioEdit v.7 bioinformatics software that UPM190 vvIBDV propagated in SPF embryonated chicken eggs resulted in amino acid changes at A279D position as early as P8. Other amino acid changes observed were N212, E249, M264, A270 and N279 at EP12 which were maintained for up to P16. However, the UPM0081 had no amino acid changes. The amino acids observed in CEF adapted viruses at P1, P5 and P10 were E249, M264, A270 and D279 except for P10 where there was a change at 279 from D to N. Similarly, the Vero adapted viruses were showing similar molecular changes with the CEF adapted strains and only P10 was showing N279 mutation. In BGM-70 cell line, UPM190 showed that P1 and P5 viruses possessed E249, M264, A270 and N279 amino acids; Q249, I264, E270 and A279 amino acids at P10 to P20. The E249Q, I264 and A270E appeared to be maintained from P10 up to P20 in the UPM190 isolates. The UPM0081 also possessed Q249, I264 and E270 amino acids at P10 to P20 which appeared to be unique. The phylogenetically, all the isolates were in the vvIBDV clade as they cluster with other reported vvIBDV sequences deposited in GeneBank. The vvIBDV UPM190 and UPM0081 propagated in BGM-70 at P15 were selected and successfully propagated in a bioreactor system with high viral yield and the bioreactor passaged viruses demonstrated the A270E amino acid changes. However, UPM190EP8 and UPM0081EP8 isolates propagated once in BGM-70 cell line and or bioreactor were lacking the E270 amino acid changes that was seen in the BGM-70 P15 or its bioreactor propagated isolate. The study showed that UPM0081 and UPM190 isolates at BGM-70 P5 and P8 when inoculated in SPF chickens did not cause any clinical signs, gross or histopathological lesions at day 7 post inoculation (pi). However, IBDV were detected in the bursa of Fabricius using RT-PCR technique. The IBDV was not detected in the bursa of Fabricius when chickens were inoculated with BGM-70 P15 IBDV isolate. In contrast, clinical signs, gross and histological lesions were observed when UPM0081 and UPM190 at EP8 were inoculated in chickens. Similarly, when the isolates EP8 isolates were propagated in BGM-70 at P1 in flask and P1 in bioreactor, the IBDVs were detected in the bursa of Fabricius by RT-PCR technique. It appeared the UPM0081 and UPM190 IBDV isolates loss their pathogenicity when passaged in BGM-70 at P15. The EP8 (EP8BGMP1) isolates propagated in bioreactor were inactivated for the development of killed IBDV vaccine. Furthermore, the study showed that day old commercial broiler chickens when inoculated with either the inactivated UPM190 (group A), inactivated UPM0081 (group B), attenuated UPM190BGMP10 (group C), attenuated UPM0081BGMP10 (group D), attenuated and inactivated UPM190 (group E) or attenuated and inactivated UPM0081 (group F) as well as the non-inoculated control group G did not cause any clinical abnormalities throughout 28 days of the trial. Grossly, bursa atrophy was recorded in the IBDV inoculated groups A to F when compared to the control group G. Histologically, overall bursa lesion scoring ranging from mild (scoring of 1) to mild to moderate (scoring of 2) were recorded in chickens from groups A to F when compared to the control group G with lesion scoring of 1 (mild) throughout the trial. The IBD antibody titre in the IBDV inoculated groups A (283±40), B (244±18) and E (253±94) were not significantly different (P>0.05) when compared to the control group (253±97) at day 28 post inoculation (pi). In contrast, the titre was significantly higher (P<0.05) in groups C (505±91), D (412±146) and F (642±187). The study also showed that no abnormal clinical signs were recorded in chickens inoculated with IBDV in all groups (A to F) at 7 days post challenged (pc) when they were challenged with vvIBDV at 21 days pi. However, in the control group F severe depression and ruffled feathers were recorded at days 3 to 6 pc, but it recovered at day 7 pc. Grossly, bursa atrophy was recorded in the IBDV inoculated groups A to F at day 7 pc. Severe bursal atrophy with hemorrhages, congestion and yellowish to red exudates in the bursal mucosa were recorded in the control group F. Histologically, overall bursa lesion scoring ranging from mild to moderate (scoring of 2) to moderate (scoring of 3) were recorded in chickens from groups A to F when compared to the control group G with lesion scoring of 4 (moderate to severe) at day 7 pc. The IBD antibody titre in the IBDV inoculated groups A (5782±1517), B (5151±1479), C (4670±787), D (4644±1359), E (7315±1838) and F (6235±1655) were significantly higher (P>0.05) when compared to the control group G (2475±991) at day 7 pc. This demonstrated that the inactivated and attenuated combination of UPM190 isolate (group E) offered the best protection against vvIBDV challenged followed in descending order by inactivated and attenuated UPM0081 combination (group F), inactivated UPM190 (group A), inactivated UPM0081 (group B), attenuated UPM190 (group C) and lastly attenuated UPM0081 (group D), suggesting that UPM190 isolate is more immunogenic when compared to UPM0081 isolate. It was concluded that the UPM190 and UPM0081 vvIBDV isolates were successfully adapted in various cell lines with high suitability to BGM-70. The vvIBDVs were attenuated following serial passaging with changes in amino acids composition at VP2 region resulting lost in pathogenicity and immunogenicity in the higher passage isolates. The vvIBDVs were successfully propagated in a bioreactor system with high titer yield for the development of attenuated and inactivated IBD tissue culture based vaccines. The chicken trials conducted showed that the bioreactor propagated IBD viruses were good immunogens that induced the production of high levels of IBD neutralizing antibodies which protected the chickens against severe bursa of Fabricius damage when challenged with vvIBDV isolate.